Crop load affects maximum daily trunk shrinkage of plum trees - Intrigliolo, Diego S.; Castel, Juan R. (2017)
We studied the effects of low fruit load (3-4 fruits cm(-2) of trunk cross-sectional area (TCSA), and high fruit load (6-7 fruits cm(-2) TCSA) on maximum daily trunk shrinkage (MDS) and trunk growth rates (TGR) over two seasons in plum (Prunus salicina Lindell) trees receiving full irrigation or deficit irrigation. Seasonal changes in MDS and TGR were compared with those in midday stein water potential (psi(s)) and leaf stomatal conductance (g(s)). Crop load increased g(s) in fully irrigated trees approaching harvest. Although crop load did not affect plant water status in either watering regime, there were considerable differences in both MDS and TGR as a function of crop load. Compared with high-cropping trees, MDS was 34% higher and TGR was 48% lower in low-cropping trees. The differential responses of MDS and psi(s) to crop load were a consequence of a higher MDS for a given psi(s) in the high-cropping trees compared with the low-cropping trees. There was a linear increase in MDS with crop load, with a slope of 15.2 pin MPa-1 per unit increment of crop load. In the fully irrigated trees, day-to-day variations in MDS were related to evaporative demand; however, the slope of the relationship between MDS and evaporative demand increased with crop load, indicating cating that different reference equations must be used to ad for tree crop load when using MDS to determine plant water status and irrigation requirements.